Jordanien: Auf den Spuren alter Kulturen - Oesch, Josef M.; Dexinger, Ferdinand (1985)
KeiBi-relevant: Hutter, Manfred, Unter dem Stiefel der Assyrer, 78-90; Trenkwalder, Helga, "Paläste" als Gräber, 142-150.